Women Entrepreneurs and Stand-up India Scheme in Punjab: A critical review - Kaur, Lakhwinder; Arora, Jyoti (Gyan Management Journal, 2022)
The study of financial inclusion has always been important for our country’s government and central bank, and it has now become even more important in light of the impact of a recession-like situation prevailing in the country. The need of the hour is to have a deeply embedded financial system that not only aids in the fight against recession but also ensures the successful operation of the nation’s financial system which is heavily reliant on the active participation of every sector of the economy. To achieve the aim of financial inclusion, the Stand-up India scheme for both women and ST/ SC entrepreneurs was launched by the government of India. The issue of the government’s responsibility for ensuring that women entrepreneurs have access to an entrepreneurial environment is of great importance. To make this scheme truly beneficial for women entrepreneurs, it should be the primary focus area for the government. This paper aims to analyze the Stand-Up India scheme from a gender perspective. The study aims to assess the Stand-Up India scheme in detail with reference to the benefits that the women entrepreneurs will get from it and to study the impact of the stand up scheme on the upliftment of women beneficiaries in Punjab. For this study, both primary and secondary sources of information have been used.